Celebrating Adam Watkins' 6th Birthday - Watkins, Howard::::::::: (1984)
Adam Watkins swinging at pink bull piñata; Greg Wille holding rope; candy on ground; Art Wille and Devon Bleile-Kratzer next to Greg